The Relationship Between Self-Efficacy and Self-Care Management with the Quality of Life of Patients With Diabetes Mellitus - Widya Galih Puspita; Anisa Catur Wijayanti (Jurnal Ilmu Kesehatan Masyarakat, 2024)
Diabetes Mellitus (DM) is a disease that suffers for years and even throughout life. DM patients have the possibility of experiencing various kinds of complications that hurt their quality of life. Factors that affect the quality of life include characteristic respondent (family history, gender, age, long-suffering of DM), self-efficacy, and self-care management. This study analyzed the relationship between self-efficacy and self-care management and the quality of life of DM patients. This quantitative study used an analytical observational approach using a cross-sectional study design with a sample size of 180 respondents, determined by a purposive sampling technique. Data was collected from respondents using a questionnaire. The research data were analyzed using logistic regression. There is a relationship between self-efficacy (p-value = 0.003) with OR (95% CI) = 7.108 (1.981 – 25.510) and self-care management (p-value 0.024) with OR (95% CI) = 3.703 (1.190 – 11.525) with quality-of-life DM patients. This study recommends that structural education programs and increased social support improve self-efficacy and self-care management to impact the quality of life of DM patients positively.